Acoustic insulation capacity of Vertical Greenery Systems for buildings. (September 2016) - Pérez, Gabriel; Coma, Julià; Barreneche, Camila; de Gracia, Alvaro; Urrestarazu, Miguel; Burés, Silvia; Cabeza, Luisa F.
Abstract: Vertical Greenery Systems (VGS) are promising contemporary Green Infrastructure which contribute to the provision of several ecosystem services both at building and urban scales. Among others, the building acoustic insulation and the urban noise reduction could be considered. Traditionally vegetation has been used to acoustically insulate urban areas, especially from the traffic noise. Now, with the introduction of vegetation in buildings, through the VGS, it is necessary to provide experimental data on its operation as acoustic insulation tool in the built environment. In this study the acoustic insulation capacity of two VGS was conducted through in situ measurements according to the UNE-EN ISO 140-5 standard. From the results, it was observed that a thin layer of vegetation (20–30 cm) was able to provide an increase in the sound insulation of 1 dB for traffic noise (in both cases, Green Wall and Green Facade), and an insulation increase between 2 dB (Green Wall) and 3 dB (Green Facade) for a pink noise. In addition to the vegetation contribution to sound insulation, the influence of other factors such as the mass factor (thickness, density and composition of the substrate layer) and type of modular unit of cultivation, the impenetrability (sealing joints between modules) and structural insulation (support structure) must be taken into account for further studies.